The Influence of Learning Mathematics in Online Learning on the Results of Mid-Semester Assessment - Zahrina Salsabila; Lintang Ega Shavira; Ibrahim Ibrahim (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
This research is a quantitative analytical survey research with an explanatory method in which the researcher attempts to explain to what extent the effect of learning mathematics on the results of mid-semester assessments for class VIII students in one of the junior high schools in Tangerang Regency. The sample of this research is students in class VIII. The sample selection was done randomly by taking 31 students from a total of 70 students. In collecting data related to student learning, we distributed a simple questionnaire by google form and to obtain data on the results of the mid-semester assessment of our students, we collaborated with the mathematics teacher in charge of the school. The results of this study stated that the way students learn in learning mathematics, especially in online learning, is said to have an effect of 11.45% on the results of the students' midterm assessment. the way to learn in online learning is divided into four sub categories of learning methods, including: how to take math lessons online, how to learn math independently at home, how to study math textbooks, and how to face math exams. Of these four sub-categories, three of them are in the good category in their implementation, while the sub-category of how to learn in online learning is in the sufficient category which indirectly means that there is still a need for re-evaluation related to the mechanism for implementing mathematics online learning.